Ca2-αLaαNb3-βXβO10 Nanosheet Photocatalyst for Hydrogen Generation from Water Splitting. (24th May 2018) - Ohmagari, Hitomi; Karim, Mohammad Razaul; Shudo, Yuta; Ida, Shintaro; Ohtani, Ryo; Hayami, Shinya
ABSTRACT: Ca2-α Laα Nb3-β X β O10 nanosheets ((α, β=0-0.14), X= Rh(LaRh), Mn(LaMn), Fe(LaFe), Ni(LaNi)) were synthesized by exfoliation using the surfactant aided sonication method. These nanosheets demonstrated superior photocatalytic activities for water splitting into hydrogen at room temperature. SEM-EDX images and spectra confirmed the morphology and composition of the materials where doped metal precursors inserted into the heterogeneous structure aided the photocatalytic activity.